EKSISTENSI PAKAIAN DI SEMENANJUNG ARAB DALAM SEJARAH ISLAM - Ahmad Sodikin; Miftahul Khoiri (JUSMA: Jurnal Studi Islam dan Masyarakat, 2023)
This article examines the existence of clothing according to Islamic history. The aim is to be able to understand the beginning of the existence of the development of clothing based on Islamic history which in the current context is referred to as the syar'i clothing model. These clothes were also associated with the social strata of society that existed at that time. This article is a literature review, using historical methods, namely: heuristics, criticism, interpretation and historiography. The results of this study indicate that clothing is an object used to cover the human body. Meanwhile, seen from its function, clothing functions as a cover for genitals, jewelry, protection and self-identity. In its development, the clothing of Muslims is still influenced by the Jahiliyah era, that is, in clothing it still shows some of their nakedness or the curves of their bodies. So that when Islam came, they rebuked him and gave advice to dress well. In its development, each region of the Arabian Peninsula has different clothing, as well as how to use it. So that people in the Arabian Peninsula who move from one region to another will be affected by the way the local people dress where they live. The types of clothing at that time included: Al-Marth, Ad-Dir, Qamish, Al-Khimar, Al-Izar and ar-Rida`. On the one hand the Arab nation is a pluralistic society consisting of various layers, namely: kings, soldiers, nobles, commoners, and so on. Therefore, the way they dress is a characteristic of the social strata in society. This can be seen from the clothes they wear which shows a prestige battle between them. Those who dress well and beautifully show that their social strata is high. On the other hand, those who dress badly show low social status. Thus the clothes have come out of their true function, as Islamic teachings are to cover the genitals, not to cover the genitals.